(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2015)
Human resources in Poland have relative advantageous features and does matter as a valuable human capital. The steady increase of the level of education of cities and villages residents, is raising their value. In the study an attempt to portray changes in the intercensal period 1988-2011 was made.